Pre-operative hypoalbuminemia is a major risk factor for anastomotic leak in emergency gastrointestinal resection and anastomosis - Anandan, Prem Kumar; Hassan, Mir Mohammed Noorul; Mathew, Mebin (International Surgery Journal, 2017)
Background: The serum albumin level is one of several clinical parameters of the status of general health. Hypoalbuminemia is known to be associated with delayed wound healing. The hypoalbuminemic state interferes with the normal functioning of the gastrointestinal tract. This study evaluates the relation of pre-operative albumin level and the risk for anastomotic leak in emergency gastrointestinal resection and anastomosis. Methods: A total of 112cases that meet the inclusion and exclusion criteria are included from Bangalore Medical College and Research Institute, Karnataka, India for a duration of 18 months November 2014 to October 2016.51 cases belonged to the stapled group and 61 cases belonged to the sutured group. Anastomosis using the two techniques, stapled and hand sewn anastomosis are evaluated separately. Results: The relation of pre-operative serum albumin and anastomotic leak is analysed in each study group separately and found that a pre-operative albumin of <3.5gm/dl is significantly associated with post-operative anastomotic leak, with a p-value of 0.0418 (p<0.05) in stapled anastomosis group and a p-value of 0.0357 (p<0.05) in hand sewn anastomosis group. Conclusions: Pre-operative albumin of <3.5gm/dl is significantly associated with post-operative anastomotic leak in both the groups, irrespective of the technique adopted.